SIFAT FISIS DAN MEKANIS PAPAN LAMINASI MENGGUNAKAN PENGAWET ALAMI BUAH BERENUK (Crescentia cujete) SEBAGAI ADITIF PADA PEREKAT TANIN: Physical Mechanical Properties of Laminated Lumber using Natural Preservatives Berenuk (Crescentia cujete) Fruit as an Additives of Tannin Adhesives - Andi Sri Rahayu Diza Lestari; Musrizal Muin; Idiahstuti (PERENNIAL, 2020)
Tannin-based adhesives have drawn interest as a research topic because they can potentially be used in the wood panel industry as an alternative for synthetic adhesives containing formaldehyde. The development of this type of adhesives is expected not only because of the high durability of the panels produced, but also because of their high strength. The aim of this study was to determine the physical and mechanical properties of laminated lumber made from mahogany (Swietenia mahagoni) bark, with the addition of a biopesticide derived from berenuk fruit (also known as calabash fruit, Crescentia cujete) and wood from jabon merah (Anthocephalus macrophyllus). Laminated lumber (2 cm x 5 cm x 40 cm in thickness, width, and length, respectively) was manufactured with two layers of lamina. The physical and mechanical properties of the laminated lumbers were tested based on JAS 234-2007 standard. The result showed that laminated board from TBRF 0% and TBRF 5% adhesives met the standard for delamination test, and all laminated boards fulfilled the standard with regard to moisture content and formaldehyde emission test.